2008
DOI: 10.1007/s12011-007-8083-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in a Combination with Magnesium Helps Reducing Negative Effects of Heat Stress in Quails

Abstract: The objective of this study was to investigate whether zinc (Zn) along with magnesium (Mg) is effective in alleviating the negative effects of heat stress in Japanese quails. One hundred and twenty 10-day-old healthy Japanese quails were randomly assigned to four treatment groups, three replicates of ten birds each. The birds were fed either a basal diet or the basal diet supplemented with either 30 mg of Zn/kg of diet, 600 mg of Mg/kg of diet, or 30 mg of Zn + 600 mg of Mg/kg of diet. The birds were kept unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
0
19
3
Order By: Relevance
“…Zinc supplementation (20 to 60 mg kg −1 diet) ameliorated oxidative stress in broiler chickens by increasing the activity of copper-zinc SOD and finally decreased lipid peroxidation (Bun et al, 2011). Furthermore it is reported that the serum malondialdehyde (MDA) concentration, an indicator of lipid peroxidation, decreases with dietary zinc supplementation in heat-stressed quails (Sahin et al, 2006;Kucuk, 2008). Sunder et al (2008) demonstrated that antibody titers against sheep red blood cells (SRBC) significantly increased in broiler chickens fed diets supplemented with zinc up to 80 mg kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc supplementation (20 to 60 mg kg −1 diet) ameliorated oxidative stress in broiler chickens by increasing the activity of copper-zinc SOD and finally decreased lipid peroxidation (Bun et al, 2011). Furthermore it is reported that the serum malondialdehyde (MDA) concentration, an indicator of lipid peroxidation, decreases with dietary zinc supplementation in heat-stressed quails (Sahin et al, 2006;Kucuk, 2008). Sunder et al (2008) demonstrated that antibody titers against sheep red blood cells (SRBC) significantly increased in broiler chickens fed diets supplemented with zinc up to 80 mg kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional strategies are important with regard to maintaining egg productivity and limiting the temperature stress using appropriate supplements (micronutrients, vitamins, minerals) in rations (Wiesinger, 2001;Heinzen and Pollack, 2003;Rodenburg et al, 2005;Lin et al, 2006;Sahin et al, 2009). In temperature stress conditions, many authors recommend the addition of zinc compounds alone or combined with other supplements in the diet because of its antioxidant and anti-stress effect (Kienholz et al, 1992;Sahin, et al, 2002Sahin, et al, , 2005Nollet et al, 2008;Kucuk, 2008;Kucuk et al, 2003Kucuk et al, , 2008. Furthermore, the addition of this element is justified by its reduced retention in the body during stress (Bartlett and Smith, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The magnesium (Mg) is the other required mineral for good health in humans and animals (Kucuk, 2008). It is needed for more than 300 biochemical reactions in the body.…”
Section: Introductionmentioning
confidence: 99%
“…It is needed for more than 300 biochemical reactions in the body. The Mg helps maintain normal muscle and nerve function, keeps heart rhythm steady, supports a healthy immune system, and keeps bones strong (Kucuk, 2008). The Mg deficiency is also related to oxidative stress in chicks, rats, and humans (Boujelben et al, 2006;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation